2005
DOI: 10.1111/j.1525-1594.2005.29099.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics of Gap Flow in a Biocentrifugal Blood Pump

Abstract: The centrifugal blood pump with a magnetically suspended impeller has shown its superiority as compared to other artificial heart pumps. However, there is still insufficient understanding of fluid mechanics related issues in the clearance gap. The design nature of the pump requires sufficient washout in the clearance between the impeller and the stationary pump housing inner surface. In this study, numerical simulations were carried out to investigate the flow fields in the gap of the Kyoto-NTN centrifugal blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…The implementations of these CFD packages are either based on the finite volume23 method or finite element method. Fluent 36, 37, 38, 39, 40, 41 and CFX 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 11, 57, 58, 59, both available from ANSYS, Inc. (Canonsburg, PA) and STAR-CD from CD-Adapco 60, 61 (Melville, New York) are the CFD software packages used most often for analysis and modelling of blood flow in VADs. In addition, AcuSolve from ACUSIM Software 62 (Mountain View, CA) and Adina from Adina R&D (Watertown, MA) are also used.…”
Section: Computational Techniquesmentioning
confidence: 99%
“…The implementations of these CFD packages are either based on the finite volume23 method or finite element method. Fluent 36, 37, 38, 39, 40, 41 and CFX 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 11, 57, 58, 59, both available from ANSYS, Inc. (Canonsburg, PA) and STAR-CD from CD-Adapco 60, 61 (Melville, New York) are the CFD software packages used most often for analysis and modelling of blood flow in VADs. In addition, AcuSolve from ACUSIM Software 62 (Mountain View, CA) and Adina from Adina R&D (Watertown, MA) are also used.…”
Section: Computational Techniquesmentioning
confidence: 99%
“…Active magnetic bearings (AMB) have been receiving widespread applications in industry [1][2][3][4][5][6]. This is because they can support the rotor without contact, thus no friction and heat are generated and the need for lubrication is also eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be thought that the leakage flow counteracts against the tendency of pressure increase in the low flow area which is shown in the pump characteristics (Fig.4). In addition, Chua et al (13) reported that Q L /Q I was 20% (Q I =6.3 L/min, Q L =1.3 L/min) at S L =0.20 mm.…”
Section: Amount Of the Gap Flowmentioning
confidence: 99%
“…According to the structure, this pump is classified as a low specific speed and low Reynolds number pump; the studies regarding such pumps conducted by Kurokawa et al [9], [10] and Matsui et al [11] may be interesting. Chua et al [12], [13] performed a numerical simulation of the internal flow when the shape of the blade was different from that of this pump, and reported that the internal flow changed according to the position of the blade due to the different velocity or pressure distribution and that the amount of flow which went through the gap corresponded to about 20% of the flow expelled by the impeller. However, there is no report which explains how the gap flow, which is characteristic to this pump, affects the entire pump system.…”
Section: Introductionmentioning
confidence: 99%